Battle Tanks : Power in the Field - Souter, Gerry (Berkeley Heights, NJ : Enslow Publishers, 2006)
Examines the role of tanks in the military, discussing special skills needed by armor crewmen and profiling specific fighting vehicles.
Crashing through! -- Tanks and their crews -- The last of the classic tanks : the M60A1 Patton -- Today's modern tank : the M1A2 Abrams -- Support team : the Bradley Fighting Vehicle -- What it takes to be an armor crewman.
Includes bibliographical references (p. 47) and index.
Keywords: Military tanks